GOOD PERSONALITIES OF TEACHER NAINA MATHUR IN “HICHKI” FILM AND ITS RELEVANCE TO THE INDONESIAN TEACHER CHARACTER REVOLUTION - Sugeng Santoso; Setyo Ajie Wibowo; Yenny Warisa Sinaga (Universitas Citra Bangsa, 2025)
This research analyzes the good personalities of Naina Mathur, a teacher in the Indian film